Kesesuaian Upah Buruh dengan Beban Kerja dalam Perspektif UU No. 13/2003 dan PP No. 36/2021 di Tegal Rejo - Nikmah Dalimunthe; Nona Pebriana Rangkuti; Adelia Sahputri Nainggolan; Namira Fariza Isnah Suglia; Sindi Rahmadani; Raya Mahfuzha; Rivandy Khairifqi; M. Wahid Daulay (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Based on Government Regulation Number 36 of 2021 about earnings and Law Number 13 of 2003 concerning Manpower, the aim of this study is to examine how workers' workloads and earnings match in Tegal Rejo Subdistrict, Medan Perjuangan District, Medan City, as well as to examine these practices from an Islamic economic perspective. The research employs a descriptive qualitative approach using library research and field interviews with workers in both formal and informal sectors. The findings indicate that formal workers generally receive regular wages and social security benefits; however, discrepancies remain between the intensity of their workload and the compensation received, especially for those working night shifts or handling high-risk tasks. Informal workers, on the other hand, face uncertain incomes, lack structured wage systems, and have minimal legal protection. These conditions fail to fully comply with the fairness principles mandated in Article 88 of Law No. 13/2003 and Articles 5 and 14 of Government Regulation No. 36/2021. From an Islamic economic standpoint, the current wage practices do not entirely reflect the principles of ujrah mitsil, distributive justice, or the goals of Islamic law (maqāṣid al-sharī‘ah), especially safeguarding the riches and welfare of workers. Enhancing pay policies that are both morally just and in line with Islamic principles is therefore essential.